(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
Technology is an essential aspect of everyday life, thus the growth and integration of information and communication technology (ICT) in learning and teaching is expected. Beginning with the origins of technology based on mathematics as a science, we narrow our focus in this scholarly study on the use of ICT in the teaching and learning of mathematics in elementary education. We focused on studying the impact of ICT on the teaching and learning process, as well as the usage of ICT tools in the development of knowledge in mathematics. The goal of this systematic analysis is to show the benefits of integrating ICT into mathematics teaching and learning, as well as the constraints and challenges that elementary school teachers and students encounter. Our comprehensive analysis of pertinent theoretical and empirical findings led us to the general conclusion that teacher proficiency with the new technology plays a major role in the integration of ICT. The positive impact of ICT on mathematics teaching and learning is undeniable, because technology reduces logistics in the planning and implementation of instruction, increases interaction in the classroom, and encourages mathematics learning through the visualization of abstract concepts and processes, while also allowing for independent study.